KEDUDUKAN HUKUM INDONESIA TERHADAP WILAYAH LANDAS KONTINEN DI BLOK AMBALAT BERDASARKAN UNCLOS 1982: The Legal Status of Indonesia regarding the Continental Shelf in the Ambalat Block based on UNCLOS 1982 - Audrey Putri Patrecia; Yulia Fitriliani (Reformasi Hukum Trisakti, 2025)
The Ambalat Block is part of the continental shelf within Indonesia's territorial waters, possessing abundant marine resources, particularly oil and natural gas. The Ambalat Block is located in the Makassar Strait, Sulawesi Sea, directly bordering Malaysia’s maritime territory. The dispute over the Ambalat Block arose when Malaysia unilaterally incorporated the area into its national map by drawing baselines from the islands of Sipadan and Ligitan. This action is contrary to the provisions of UNCLOS 1982, which stipulates that drawing baselines from outermost islands can only be conducted by archipelagic states. Therefore, the research question addressed in this article is: What is Indonesia's legal standing regarding the continental shelf in the Ambalat Block based on UNCLOS 1982? This article employs normative legal research and adopts a descriptive approach, utilizing secondary data collected through library research. The discussion and conclusions derived indicate that Indonesia, as an archipelagic state, has the right to draw baselines in accordance with Article 76 of UNCLOS 1982, which governs the continental shelf. In resolving the dispute, Indonesia applies the double-line theory to determine its maritime boundaries, grounded in the principle of equity as stipulated in Article 83 of UNCLOS 1982.